Design parameters of a reluctance actuation system for stable operation conditions with applications of high‐precision motions in lithography machines - Mohammad Al Saaideh; Natheer Alatawneh; Mohammad Al Janaideh (IET Electric Power Applications, 2022)
Abstract Recently, the reluctance actuator has attracted great attention to replace the Lorentz actuator in the next generation of wafer scanners in semi‐conductor lithography machines. The reluctance actuator has a non‐linear position‐force characteristic, which may cause high oscillations and unstable operation. This study presents a linearisation technique by optimising the main parameters of the reluctance actuator to operate away from the saturation point. Also, in this study, the critical current is formulated for the stable dynamic behaviour of the reluctance actuator. Optimisation based on the Grey Wolf Optimiser is performed considering the high‐precision motion requirements and physical constraints. The high‐precision motion requirements include the desired work‐space displacement, natural frequency, and maximum force. The electromechanical dynamic model of the reluctance actuator motion system is formulated to characterise the interaction among electrical, magnetic, and mechanical parts. The simulation results show that the optimal design of the reluctance actuator works in the linear region, and for stable dynamic behaviour, the input current is limited by the critical current. Finally, a feedforward controller is designed based on the approximation of the force–current relationship to improve the tracking performances of the reluctance actuator motion system. The simulation results in time and frequency domains show an improvement in tracking performances using the feedforward controller.